Skin test concentrations for systemically administered drugs – an ENDA/EAACI Drug Allergy Interest Group position paper. Issue 6 (25th April 2013) - Brockow, K.; Garvey, L. H.; Aberer, W.; Atanaskovic‐Markovic, M.; Barbaud, A.; Bilo, M. B.; Bircher, A.; Blanca, M.; Bonadonna, B.; Campi, P.; Castro, E.; Cernadas, J. R.; et al.
Abstract Skin tests are of paramount importance for the evaluation of drug hypersensitivity reactions. Drug skin tests are often not carried out because of lack of concise information on specific test concentrations. The diagnosis of drug allergy is often based on history alone, which is an unreliable indicator of true hypersensitivity.To promote and standardize reproducible skin testing with safe and nonirritant drug concentrations in the clinical practice, the European Network and European Academy of Allergy and Clinical Immunology (EAACI) Interest Group on Drug Allergy has performed a literature search on skin test drug concentration in MEDLINE and EMBASE, reviewed and evaluated the literature in five languages using the GRADE system for quality of evidence and strength of recommendation. Where the literature is poor, we have taken into consideration the collective experience of the group.We recommend drug concentration for skin testing aiming to achieve a specificity of at least 95%. It has been possible to recommend specific drug concentration for betalactam antibiotics, perioperative drugs, heparins, platinum salts and radiocontrast media. For many other drugs, there is insufficient evidence to recommend appropriate drug concentration. There is urgent need for multicentre studies designed to establish and validate drug skin test concentration using standard protocols. For most drugs, sensitivity of skin testing is higher in immediate hypersensitivity compared to nonimmediate hypersensitivity.